Poor-quality medical research: what can journals do? - Altman, D (2002)
The aim of medical research is to advance scientific knowledge and hence--directly or indirectly--lead to improvements in the treatment and prevention of disease. Each research project should continue systematically from previous research and feed into future research. Each project should contribute beneficially to a slowly evolving body of research. A study should not mislead; otherwise it could adversely affect clinical practice and future research. In 1994 I observed that research papers commonly contain methodological errors, report results selectively, and draw unjustified conclusions. Here I revisit the topic and suggest how journal editors can help.